NILAI MORAL YANG TERDAPAT DALAM NOVEL DUA GARIS BIRU KARYA LUCIA PRIANDARINI DAN GINA S. NOER - Rangkuti, Nanda Syafitri; Husna, Tiflatul (Jurnal Bahastra, 2022)
This research focuses on problems related to the form of moral values teaching, and the elements of story building that are used to convey the moral values contained in the novel Dua Garis Biru by Lucia Priandarini and Gina S. Noer. Data collection was carried out by means of reading and note-taking techniques, then data analysis was carried out by using qualitative descriptive method techniques. The research instrument used was the researcher himself and was assisted by a friend to research the novel so that the data obtained was more accurate. Based on the results of research that has been carried out regarding the moral values in the novel Dua Garis Biru by Lucia Priandari and Gina S. Noer, there are 10 aspects in it, namely Assertive, Forgiving, True to Promises, Living in Harmony, Deliberation, Caring for Others, Please Help, Pray to God, Respect Others, and Parental Love for Children. The moral values in the novel make various problems that exist to be resolved because of concern, help each other, and various problems that can be discussed and discussed will find ways to solve them.